Estimating the dimensions of integrated calciner and carbonator for calcium looping process in a 7500 TPD capacity of cement plant - Aulia, Tia; Prahmana, Rico Aditia; Darmanto, Prihadi Setyo; Juangsa, Firman Bagja; Ghita Ghaida Permatasari, Raden Dewi; Walad, Khoeril (National Research and Innovation Agency, 2024)
The calciner in cement factories plays a crucial role, particularly in the decomposition of calcium carbonate (CaCO3) as primary raw materials into calcium oxide (CaO) and carbon dioxide (CO2), a significant contributor to greenhouse gas (GHG) emissions. Hence, an integrated system has been proposed, combining conventional cement plants with calcium looping (CaL) cycles to reduce CO2 emissions. CaL facilitates the capture of CO2 by CaO, forming CaCO3 as raw material for cement production. Given that CaL effectively reduces CO2 emissions, the integration process with conventional cement plants requires careful consideration, particularly regarding raw materials, calciners, and carbonators. Integration parameters for CaL in raw materials include average diameter and logarithmic temperature difference. At the same time, calciners and carbonators encompass heat transfer coefficient (U), calciner dimensions, carbonation factor, and mass balance post-integration with CaL. These parameters will be calculated to facilitate the integration of the CaL cycle with conventional cement plants. In this study, based on raw materials with an average diameter of 3.28 µm and the mean heat transfer coefficient between hot gas and raw materials of 4 W/m2 K, the calculated dimensions for the calciner are 9.6 m in diameter and 25 m in height. Since the plant studied has two preheater strings, two carbonator units are also required. The size of each carbonator is 4.75 m in diameter with a length of about 40 m, so it has a total volume approximately equal to the volume of the calciner to provide a longer residence time for particles.